The term cross and Crusader (Frankish) and the Kurdish singularity in historical writings on its name? (Journal of the College of Basic Education, 2022)
The research aims to clarify the term Crusader and the uniqueness of the Kurds in the Kurdish historical writings around its name, and to clarify the history of the cross in the past and in the Christian medieval era and then transformed into a symbol and slogan since the recognition of Christianity during the time of Emperor Constantine I, and the term crusade during campaigns in the writings and European languages ​​and Muslim historians, and neighboring peoples that On the history of the Crusades, we find an amazing irony in the contemporary writings of the Kurds for their use of the formula (kach Parst, i.e. worshipers of the cross). The clarification of these paradoxes is grappling with the term around the term, although Muslim and Arab historians of the Frankish campaigns on the lands of the Islamic East and Jerusalem have written about these campaigns in the terms (Frankish wars), and they have always described them as the term (Frankish) and clarify the history and origin of the Frankish term for Muslim and Arab historians and The Romans, a reference to the term naming the term for Western peoples, show the beginnings of the use of the term Crusades, and the cross between religious belief and political employment.